Nanomaterials as carriers to improve the photodynamic antibacterial therapy - Liu, Houhe; Jiang, Yuan; Wang, Zhen; Zhao, Linping; Yin, Qianqian; Liu, Min (Frontiers in Chemistry, 2022)
The main treatment for bacterial infections is antibiotic therapy, but the emergence of bacterial resistance has severely limited the efficacy of antibiotics. Therefore, another effective means of treating bacterial infections is needed to alleviate the therapeutic pressure caused by antibiotic resistance. Photodynamic antibacterial therapy (PDAT) has gradually entered people's field of vision as an infection treatment method that does not depend on antibiotics. PDAT induces photosensitizers (PS) to produce reactive oxygen species (ROS) under light irradiation, and kills bacteria by destroying biological macromolecules at bacterial infection sites. In recent years, researchers have found that some nanomaterials delivering PS can improve PDAT through targeted delivery or synergistic therapeutic effect. Therefore, in this article, we will review the recent applications of several nanomaterials in PDAT, including metal nanoclusters, metal-organic frameworks, and other organic / inorganic nanoparticles, and discuss the advantages and disadvantage of these nanomaterials as carriers for delivery PS to further advance the development of PDAT.